P9 Intensification of grazing and productive performance and enteric methane emissions from ruminants in the high Andean sites - Grijalva, J.E. (2023)
In the high Andean hillside sites, indigenous populations use their lands mainly for grazing of sheep and cattle. Animal response depends exclusively on the quality of forage and the physical and chemical conditions of the soil. Here, we investigated whether an increased on grazing intensification regulates the nutritional profile on forage and soil properties, and whether those parameters play a key role on the animal performance and enteric methane emissions of the grazing ruminants. At altitudes of 3 500–3 700 and 3 200–3 400 m, soil samples were taken to analyze the chemical profile and bulk density of soil. We evaluated the use of natural grasslands based on Stipa Ichu moor straw at harvesting frequencies of 75 days and improved pastures composed of perennial ryegrass Lolium perennial and white clover Trifolium repens used at 45 and 60 days. For this purpose, chemical composition analyses were performed and animal carrying capacity, milk yield and enteric CH4 emissions were estimated. In sheep blood serum, the blood profile of Ca, P, Mg and the activity of Alkaline Fosphathase (AF) and Alanine Amino Transferase (ALT) enzymes were analyzed. In the soils, 6.28 and 6.10 of pH, 7.35 and 5.13% Organic Matter (MO), 0.37 and 0.25%Total Nitrogen (N), 26.21 and 2.67ppm Phosphorus (P), 0.37 and 0.27cmol Potasium (K)/kg, 13.26 and 8.62 cmol Ca/kg; 3.47 and 2.18 cmol Mg/kg were found at high and low altitudinal levels, respectively. The comparison of pastures yielded the following results: 18.2 and 9.9% Crude Protein (CP), 20.2 and 20.9% Crude Fiber (CF), 44.2 and 42.1% Neutral Detergent Fiber (NDF), 29.3 and 30.8% Acid Detergent Fiber (ADF); 2.4 and 2.1 Mcal of Metabolizable Energy (ME)/Kg Dry Matter (DM) at 45 and 60 days of harvesting interval, respectively. The natural prairie on the other hand, used at frequencies of 75 days yielded 3.9% CP; 34.3% CF, 58.5% NDF, 42.0% ADF and 1.6 Mcal ME/Kg DM. Milk production decreased from 11.0 to 7.0 and <1.0 L ha-1day-1 and emissions decreased from 7.56 to 7.38 and 7.19% of CH4 in relation to the Gross Energy (GE) consumed, in the scenarios of pastures of 45 and 60 days of frequency of harvesting vs 70 days with the natural meadow. The blood mineral profile was apparently normal among the pasture alternatives, reflecting 9.2% ± 1.85 Ca, 7.2% ± 1.79 P and 2.4% ± 0.22 Mg. The activity of ALT and AF enzymes were as high as 130.6 and 259.6 U/L, in that order. The results show that the intensification of pasture management and grazing through harvesting at frequencies of 45 days or less, are productive and low-emission options, given the greater efficiency of the pastures in relation to natural grassland. Thanks to University Central of Ecuador.